비전형적 성역할 교육프로그램이 유치원아의 성역할 고정관념에 미치는 영향 - 염명순(Myung Soon Yum); 조복희(Bok Hee Cho); 권희경(Hee Kyoung Kwon); 한유미(You Me Han) (Korean Journal of child studies, 1999)
This study used reversed sex-typed programs as an educational tool to teach preschool children about varieties of sex roles. The subjects were 85 four- and five-year-old kindergarten children, half of whom were assigned to the experimental group and half to the control group. The children's sex role stereotypes decreased after participation in reversed sex-typed programs. Girls' scores of sex role stereotypes were higher in terms of own sex and in child and adult activity but lower in terms of the opposite sex than those of boys. There were differences in the scores of sex-role stereotypes in terms of child activity and adult activity.